EFEKTIVITAS METODE BERMAIN JIGSAW PUZZLE DALAM KEMAMPUAN MENGGUNAKAN PAKAIAN PADA ANAK BERKEBUTUHAN KHUSUS - Nadia Relenia Relenia Pane; Herlina " "; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Different ability people (Diffable) are they who have sensorimotor and mental resistance so that interfere their growth and progress naturally until they need to be treated specially. The aim of this research was to determine the effect of jigsaw puzzle game method in dress up ability toward the diffable. The research used quasy experiment with non-equivalent control group design. This research was conducted in SLB Pembina Pekanbaru through 34 respondents that taken by using purposive sampling technique which are divided into 17 respondents as experimental group and 17 respondents as control group. The instrument in this research was observational sheet about how to dress up, with number that should be observed is about 5 items; shirt, t-shirt, pants, sock, and shoe. The analysis used  univariate and bivariate with dependent sample t test and independent sample t test. The most characteristic respondents is 10 years old (50%), the most of participants are second grade (52,94%), the most of participants are male (55,88%), the  most of participants are mental retardation (64,70%). The result of this research represents p value = 0,001 < α (0,05), it mean there is significant difference after treatment by jigsaw puzzle game method. The conclusion of this research means that Jigsaw Puzzle Game method can increase the ability of dressing-up toward the diffable. Based on the result, school is expected to use puzzle game technique in modifying teaching method toward the diffable to increase their ability in dressing-up. Keyword                : Different ability people (Diffable), jigsaw puzzle, dress-up ability